(untitled) (LEARNing Landscapes, 2008)
This case study uses adolescents’ accounts of studio practice to trace the diverse themes, sources, and contexts that inspire aesthetic and narrative meaning in their artworks. Beyond self expression and formal and technical concerns, the study illustrates how eight young artists work to address cultural and aesthetic themes that borrow, build on, and ultimately reinvent conventional narratives and art forms. Narrative formation, and its relevance for learning and teaching art, is investigated as distinct but related practices in multiple worlds of art, cultures, and education.